PENGARUH TEKNIK TRACING THE DOTS TERHADAP KETERAMPILAN MENULIS SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS II SDN 3 MARIA - Sarina; Muhammad Ajwar; Nunung Fatimah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Basic education is an important foundation in the formation of language skills, one of which is writing skills. However, observations at SDN 3 Maria showed that many second-grade students still had difficulty writing, characterized by inconsistent letter shapes, less neat writing, and difficulty writing cursive letters. This condition is exacerbated by monotonous writing learning methods, so a more innovative approach is needed. This study aims to test the effect of the tracing the dots technique on students' writing skills in the Indonesian language subject for second-grade students at SDN 3 Maria. A quantitative approach with a one-group pretest-posttest pre-experimental design was used, with a sample of 20 students selected through purposive sampling. Data were collected through writing tests (pretest and posttest) and classroom observations, then analyzed descriptively and using paired t-tests. The results showed a significant increase in students' writing skills after the application of the tracing the dots technique. The average writing score increased from 6.5 in the pretest to 10.5 in the posttest, especially in terms of correct letter formation, neatness of writing, and consistency of spacing between letters and words. In addition, the application of this technique also increased students' motivation and confidence in writing. Theoretically, these findings enrich insights into writing learning strategies at the elementary school level. Practically, the results of this study are useful for teachers and schools in choosing effective and enjoyable writing learning methods for students.